Encapsulation of palladium porphyrin photosensitizer in layered metal oxide nanoparticles for photodynamic therapy against skin melanoma. Issue 5 (9th October 2015) - Chen, Zih-An; Kuthati, Yaswanth; Kankala, Ranjith Kumar; Chang, Yu-Chuan; Liu, Chen-Lun; Weng, Ching-Feng; Mou, Chung-Yuan; Lee, Chia-Hung
Abstract: We designed a biodegradable nanocarrier of layered double hydroxide (LDH) for photodynamic therapy (PDT) based on the intercalation of a palladium porphyrin photosensitizer (PdTCPP) in the gallery of LDH for melanoma theragnosis. Physical and chemical characterizations have demonstrated the photosensitizer was stable in the layered structures. In addition, the synthesized nanocomposites rendered extremely efficacious therapy in the B16F10 melanoma cell line by improving the solubility of the hydrophobic PdTCPP photosensitizer. The detection of singlet oxygen generation under irradiation at the excitation wavelength of a 532 nm laser was indeed impressive. Furthermore, the in vivo results using a tumour xenograft model in mice indicated the apparent absence of body weight loss and relative organ weight variation to the liver and kidney demonstrated that the nanocomposites were biosafe with a significant reduction in tumour volume for the anti-cancer efficacy of PDT. This drug delivery system using the nanoparticle–photosensitizer hybrid has great potential in melanoma theragnosis.